1989
DOI: 10.2169/internalmedicine1962.28.189
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA(S-IgA) levels in sera from patients with diffuse panbronchiolitis.

Abstract: The serum S-IgA levels of 33 patients with diffuse panbronchiolitis (DPB) were compared with those of 13 patients with chronic bronchitis (CB) and 24 patients with bronchiectasis (BE), to obtain information on differences in the pathologic states in DPB and other chronic bronchial diseases. The S-IgA levelw as elevate in all three bronchial diseases, being significantly higher in DPB than in CB, and intermediate in BE. Persistent bacterial infections developed in most of the patients with DPB and two-thirds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…S-IgA is secreted locally from the airway walls onto the mucous membrane and is believed to play an important role in protecting the mucous membrane from infection (3,4). Previously we have reported that the levels of serum IgA and S IgA, particularly the latter, are elevated in patients with diffuse panbronchiolitis and severe brochiectasis (5). However, the mechanism of response of the local and systemic IgA systems to persistent respiratory infection with Pseudomonas aeruginosa is non known in these disease.…”
Section: Introductionmentioning
confidence: 99%
“…S-IgA is secreted locally from the airway walls onto the mucous membrane and is believed to play an important role in protecting the mucous membrane from infection (3,4). Previously we have reported that the levels of serum IgA and S IgA, particularly the latter, are elevated in patients with diffuse panbronchiolitis and severe brochiectasis (5). However, the mechanism of response of the local and systemic IgA systems to persistent respiratory infection with Pseudomonas aeruginosa is non known in these disease.…”
Section: Introductionmentioning
confidence: 99%